2018
DOI: 10.1186/s12936-018-2548-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug resistance associated genetic diversity in Mauritanian isolates of Plasmodium vivax reveals limited polymorphism

Abstract: BackgroundPlasmodium vivax is the predominant malaria species in northern Mauritania. Molecular data on P. vivax isolates circulating in West Africa are scarce. The present study analysed molecular markers associated with resistance to antifolates (Pvdhfr and Pvdhps), chloroquine (Pvmdr1), and artemisinin (Pvk12) in P. vivax isolates collected in two cities located in the Saharan zone of Mauritania.MethodsBlood samples were obtained from P. vivax-infected patients recruited for chloroquine therapeutic efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
4
8
3
Order By: Relevance
“…However, the same studies reported between 10 and 20% of infections to have double mutant alleles of dhfr (combinations of variants at codons 58, 61 and 117) [38, 39], in contrast to results here that showed an absence of resistance-associated alleles at these codons (except for a single variant at codon 117 in infection sample NKT136 that had an overall genotype similar to Asian parasites). Antimalarial antifolate use in Mauritania is now limited to intermittent preventative treatment of pregnant women with sulphadoxine-pyrimethamine [38], although antifolates were previously used for therapy along with chloroquine. Comparing this and previous studies, the frequency of the mdr1 976F allele in Mauritania varied from 28% in 2007-9 to 14% in 2012-13, and 4% in 2013-16 [38, 39], which may reflect a decline due to fitness cost after chloroquine use officially stopped following introduction of Artemisinin Combination Therapy in 2006, although the allele is not a marker of chloroquine resistance and is at most a minor modulator [16].…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…However, the same studies reported between 10 and 20% of infections to have double mutant alleles of dhfr (combinations of variants at codons 58, 61 and 117) [38, 39], in contrast to results here that showed an absence of resistance-associated alleles at these codons (except for a single variant at codon 117 in infection sample NKT136 that had an overall genotype similar to Asian parasites). Antimalarial antifolate use in Mauritania is now limited to intermittent preventative treatment of pregnant women with sulphadoxine-pyrimethamine [38], although antifolates were previously used for therapy along with chloroquine. Comparing this and previous studies, the frequency of the mdr1 976F allele in Mauritania varied from 28% in 2007-9 to 14% in 2012-13, and 4% in 2013-16 [38, 39], which may reflect a decline due to fitness cost after chloroquine use officially stopped following introduction of Artemisinin Combination Therapy in 2006, although the allele is not a marker of chloroquine resistance and is at most a minor modulator [16].…”
Section: Discussioncontrasting
confidence: 63%
“…Analysis of dhfr and dhps genotypes revealed a virtual absence of antifolate resistance-associated variants in P. vivax in Mauritania. Consistent with this, drug resistance genotyping of P. vivax samples previously taken from Nouakchott in 2007-9 and 2013-16 also showed no resistance-associated alleles in dhps [38, 39]. However, the same studies reported between 10 and 20% of infections to have double mutant alleles of dhfr (combinations of variants at codons 58, 61 and 117) [38, 39], in contrast to results here that showed an absence of resistance-associated alleles at these codons (except for a single variant at codon 117 in infection sample NKT136 that had an overall genotype similar to Asian parasites).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Consistent with this, drug resistance genotyping of P. vivax samples previously taken from Nouakchott in 2007-9 and 2013-16 also showed no resistance-associated alleles in dhps [41,42]. However, the same studies reported between 10 and 20% of infections to have double mutant alleles of dhfr (combinations of variants at codons 58, 61 and 117) [41,42], in contrast to results here that showed an absence of resistance-associated alleles at these codons (except for a single variant at codon 117 in infection sample NKT136 that had an overall genotype similar to Asian parasites). Antimalarial antifolate use in Mauritania is now limited to intermittent preventative treatment of pregnant women with sulphadoxine-pyrimethamine [41], although antifolates were previously used for therapy along with PLOS NEGLECTED TROPICAL DISEASES chloroquine.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 78%